This is Shakespeare - Smith, Emma 1970- (Pelican, an imprint of Penguin Books, 2019)
Is this Shakespeare? Well, sort of. But it doesn't really tell us the whole truth. So much of what we say about Shakespeare is either not true, or just not relevant, deflecting us from investigating the challenges of his inconsistencies and flaws. This electrifying new book thrives on revealing, not resolving, the ambiguities of Shakespeare's plays and their changing topicality. It introduces an intellectually, theatrically and ethically exciting writer who engages with intersectionality as much as with Ovid, with economics as much as poetry: who writes in strikingly modern ways about individual agency, privacy, politics, celebrity and sex. It takes us into a world of politicking and copy-catting, as we watch him emulating the blockbusters of Christopher Marlowe and Thomas Kyd, the Spielberg and Tarantino of their day; flirting with and skirting round the cut-throat issues of succession politics, religious upheaval and technological change. The Shakespeare in this book poses awkward questions rather than offering bland answers, always implicating us in working out what it might mean. This is Shakespeare. And he needs your attention
Enthält bibliographische Angaben (Seite 325-337) und Index.
Keywords: Shakespeare, William / 1564-1616; Shakespeare, William / 1564-1616 / Criticism and interpretation; Shakespeare, William; 1564-1616; fast; (OCoLC)fst00029048; Criticism, interpretation, etc; fast; (OCoLC)fst01411635